(3SaQ GdSYGOIs - (3eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, CHh WGgQ, eLO GdOjf GdTjQGRj GdajQhRBHGOj,(B817 (3g`s ((3CHhHcQ Hf efLc s)
(3ChdgG (B:s
(3HYO GdMeO hGdKfGA Ydi MVQI Pj GdcHQjGA hGdUdGI HdG EfJgGA Cf WQjb GdMb GdPj gh GdUQGW GdeSJbje s
(3BNQgG (B:s
(3hHGH EaJQGb GdCeI Edi EKfjf hSHYjf aQbI de jKHJ ajg Tj hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B191s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs